The Use Of Drills And Picture To Vocabulary Mastery Of The Sixth Year Students Of Sd Negeri 1 Gedung Sari, Anak Ratu Aji, Lampung Tengah In The Academic Year Of 2011/2012 - Muhammad Kristiawan (Universitas Bandar Lampung, 2011)
Teaching vocabulary successfully needs a good method. The method of teaching vocabulary is always changeable. It is due to teaching itself is a complicated process that never possible gives absolute rule, which will ensure success. At this point, teacher is necessary to use best guide. The drill and picture method represent a multisensory multifaceted approach suitably needed by different students. The benefits from this research are: (1). to know the scaffold of the drill and picture method to vocabulary mastery of the students. (2). to develop and enrich knowledge in method of vocabulary mastery. (3). to add discourse of effective studying English for increasing students achievements in general and vocabulary mastery in particular.The object of this research is the population of academic members of SD Negeri 1 Gedung Sari, Anak Ratu Aji, Lampung Tengah in the academic year of 2011/2012. The sample of the study is the second year students of SD Negeri 1 Gedung Sari and it is called as total sample because it just consists of one class. There are 24 students in this class. To get the data for writing down this thesis, the writer applied several methods and can be divided into three types, there are: document study, field research, and statistical methods.Document study applied by studying about documents which are available in the second year of SD Negeri I Gedung Sari in the academic year of 2011/2012. Field research consists of questioner, test and observation. The researcher used the data from field research to analyze the problems which will be answered in this article. The last analysis is statistical methods.The writer uses formula of product moment correlation to measure how significant the influence eclectic reading method toward reading comprehension achievement. (1). Based on applied several methods above, the researcher discovered the result that: The score of eclectic reading method of the second year students or SD Negeri 1 Gedung Sari according to the writer is significant, proven from the percentage questioner scores. It is 66 % (2). The English reading comprehension achievement of the second year students of SD Negeri I Gedung Sari is significant, proven from the percentage of English reading comprehension score. It is 71, 67%. (3). The next statistical hypothesis that says there is no correlation between eclectic reading method (X) and students English reading comprehension achievement (Y) is refused because after consulting the critical r in the level of significant of 5% found that critical r for the number of samples 24 is 0,404. In other words, it can be said that research hypothesis says there is significant correlation between eclectic reading method and students English reading comprehension achievement is proved.